2017
DOI: 10.1007/s13760-017-0816-5
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s disease CSF biomarkers: clinical indications and rational use

Abstract: This review focusses on the validation and standardization of Alzheimer’s disease (AD) cerebrospinal fluid (CSF) biomarkers, as well as on the current clinical indications and rational use of CSF biomarkers in daily clinical practice. The validated AD CSF biomarkers, Aβ1-42, T-tau, and P-tau181, have an added value in the (differential) diagnosis of AD and related disorders, including mixed pathologies, atypical presentations, and in case of ambiguous clinical dementia diagnosis. CSF biomarkers should not be r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
85
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 85 publications
0
85
0
3
Order By: Relevance
“…In AD subjects, the CSF concentration of Aβ 42 decreases over time, while 181-phospho-tau and total tau concentrations increase, when compared to healthy controls (including patients with psychiatric disorders such as depression) [ 110 ]. CSF studies have shown that the combined measurement of CSF Aβ 42 , total tau, and 181-phospho-tau levels can diagnose AD [ 111 ] with a sensitivity and specificity reaching 92 and 89%, respectively [ 112 ]. Other studies have suggested an assay using Aβ 42 and T-tau levels can accurately discriminate AD from controls by means of a discrimination line, which has been validated in clinical practice [ 113 ] and in autopsy-confirmed patients, with sensitivity levels of 100% and specificity of 91% [ 114 ].…”
Section: Biomarkers: Preferably Peripheralmentioning
confidence: 99%
“…In AD subjects, the CSF concentration of Aβ 42 decreases over time, while 181-phospho-tau and total tau concentrations increase, when compared to healthy controls (including patients with psychiatric disorders such as depression) [ 110 ]. CSF studies have shown that the combined measurement of CSF Aβ 42 , total tau, and 181-phospho-tau levels can diagnose AD [ 111 ] with a sensitivity and specificity reaching 92 and 89%, respectively [ 112 ]. Other studies have suggested an assay using Aβ 42 and T-tau levels can accurately discriminate AD from controls by means of a discrimination line, which has been validated in clinical practice [ 113 ] and in autopsy-confirmed patients, with sensitivity levels of 100% and specificity of 91% [ 114 ].…”
Section: Biomarkers: Preferably Peripheralmentioning
confidence: 99%
“…Biomarkers have been incorporated into research diagnostic criteria for AD [ 12–14 ] and, although the clinical examination (including full neuropsychological evaluation) is still the basis for AD diagnosis [ 1 ], these biomarkers are being introduced in daily clinical practice as in vivo surrogate markers for the confirmation of AD neuropathology. The core CSF AD biomarkers increase the diagnostic accuracy for diagnosing AD (mainly in cases with atypical presentations), also in its prodromal phase (mild cognitive impairment (MCI) due to AD) [ 15, 16 ] and are able to differentiate between AD and psychiatric disorders [ 17 ]. The CSF biomarkers are useful to diagnose AD in patients with ambiguous clinical dementia diagnoses [ 4 ] and in cases with mixed brain pathology like AD with cerebrovascular disease [ 5, 18, 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, cerebrospinal fluid (CSF) Aβ was suggested as an alternative biomarker for the amyloid concentration measurement by the 2018 revision of AD diagnostic criteria by National Institute on Aging and Alzheimer's Association (NIA-AA) [5][6][7][8]. Measurements of CSF Aβ show high diagnostic accuracy [9,10]. It is notable that, while Aβ concentration increase and soluble oligomers and insoluble plaques build up in the brain, the alteration of Aβ levels in CSF shows a proportionally inverse behavior.…”
Section: Introductionmentioning
confidence: 99%